2018
DOI: 10.1177/2333721418800064
|View full text |Cite
|
Sign up to set email alerts
|

Public Employment Policy for an Aging Workforce

Abstract: Americans are working longer. For many older workers, employment earnings are essential for self-sufficiency. When older workers are forced to change jobs, they suffer bigger earnings losses and take longer to find new jobs than prime-age workers. Unfortunately, public workforce policy has not adapted to serve older workers. Our strategic survey of published research evidence and government statistics suggests a variety of ways that employment programs could be adapted to benefit older workers. In this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Some studies have revealed that there are differences between in employment by age groups, for example, Wandner and his colleagues (Wandner, et al, 2018) have indicated that there are serious problems for older workers to be employed in the U.S., because the public workforce system is not adapted to serve older workers as they need more in-person, one-on-one services including consulting and placement services. In developed countries it is paid a lot of attention of involvement of elderly in several social activities and to those aspects are devoted many researches (Cho, Kim, 2019) including also subjective aspects.…”
Section: Employment Differences In Latvia: Theoretical Frameworkmentioning
confidence: 99%
“…Some studies have revealed that there are differences between in employment by age groups, for example, Wandner and his colleagues (Wandner, et al, 2018) have indicated that there are serious problems for older workers to be employed in the U.S., because the public workforce system is not adapted to serve older workers as they need more in-person, one-on-one services including consulting and placement services. In developed countries it is paid a lot of attention of involvement of elderly in several social activities and to those aspects are devoted many researches (Cho, Kim, 2019) including also subjective aspects.…”
Section: Employment Differences In Latvia: Theoretical Frameworkmentioning
confidence: 99%